Mind mapping: tools for creativity development - Koliada, I. V.; Sukhanova, Tetiana Yevhenivna; Vnukova, K. V. (Видавничий дім "Гельветика", 2024)
The mind mapping method contributes to the implementation of one of the main pedagogical principles i.e. the principle of clarity. Mind maps allow you to visually cover the full range of English lexical and grammatical topics, presenting the most important aspects through associative links and comparisons. Mind mapping, or the creation of mind maps, is a powerful tool that helps to implement the principle of visualization in education, especially in the study of foreign languages. This technology allows you to transform complex linguistic information into simple and understandable images, which greatly facilitates the learning and memorization process. Instead of just reading or listening to new words and grammar rules, students can visualize them, which improves understanding and learning of the material. One of the main tools of creativity in mind mapping is the ability to create associative connections. In foreign language learning, this means that new words and phrases can be connected to other words already known to the student through logical or emotional connections. For instance, the word "apple" can be associated with the word "fruit" or even with a specific color, which helps to better remember the new word. This approach helps to see the big picture and better understand the context, which is especially important when learning a new language. In addition, mind maps are actively used to develop creative thinking in language learning. They help students generate new ideas about how to remember words, sentence structures, and grammar rules because the process of creating a map stimulates the brain to find new connections and associations. Creativity in this context becomes an important component of successful foreign language learning. Modern technologies greatly simplify the process of creating mental maps for learning languages. There are many programs and applications that allow you to quickly and conveniently create, edit and save intelligence maps dedicated to learning foreign languages. This makes mind mapping accessible to a wide range of users, from pupils and students to teachers and professionals looking to learn a new language. The relevance of mind mapping in foreign language learning continues to grow, as modern challenges require new approaches to learning. In a world where language competence is becoming increasingly important, the ability to effectively organize information and use it to learn a new language is critical. Mind mapping helps to solve these tasks by providing students with a tool for deeper understanding and better memorization of language material.

Метод майндмепінгу(mindmapping) сприяє реалізації одного з основних педагогічних принципів – принципу наочності. Ментальні карти дозволяють візуально охопити всю різноманітність лексичних та граматичних тем англійської мови, представляючи найважливіші аспекти через асоціативні зв’язки та порівняння. Майндмепінг, або створення інтелект-карт, є потужним інструментом, який допомагає реалізувати принцип наочності в освіті, особливо у вивченні іноземних мов. Ця технологія дозволяє перетворити складну лінгвістичну інформацію на прості та зрозумілі образи, що значно полегшує процес навчання і запам’ятовування. Замість того, щоб просто читати або слухати нові слова і граматичні правила, студенти можуть візуалізувати їх, що покращує розуміння та засвоєння матеріалу. Одним із головних інструментів креативності в майндмепінгу є можливість створювати асоціативні зв’язки. У вивченні іноземних мов це означає, що нові слова та фрази можуть бути пов’язані з іншими словами, які вже відомі студенту, через логічні або емоційні зв’язки. Наприклад, слово "яблуко" може бути асоційоване зі словом "фрукт" або навіть із конкретним кольором, що допомагає краще запам’ятати нове слово. Такий підхід допомагає побачити загальну картину і краще зрозуміти контекст, що особливо важливо при вивченні нової мови. Крім того, ментальні карти активно використовуються для розвитку креативного мислення у вивченні мов. Вони допомагають студентам генерувати нові ідеї щодо того, як запам’ятовувати слова, структури речень та граматичні правила, оскільки процес створення карти стимулює мозок знаходити нові зв’язки та асоціації. Креативність у такому контексті стає важливою складовою успішного вивчення іноземної мови. Сучасні технології значно спрощують процес створення ментальних карт для вивчення мов. Існує безліч програм та додатків, які дозволяють швидко і зручно створювати, редагувати та зберігати інтелект-карти, присвячені вивченню іноземних мов. Це робить майндмепінг доступним для широкого кола користувачів, від учнів і студентів до викладачів та професіоналів, які прагнуть вивчити нову мову. Актуальність майндмепінгу у вивченні іноземних мов продовжує зростати, оскільки сучасні виклики вимагають нових підходів до навчання. У світі, де мовна компетенція стає все більш важливою, вміння ефективно організовувати інформацію і використовувати її для засвоєння нової мови є критично важливим. Майндмепінг допомагає вирішити ці завдання, надаючи студентам інструмент для глибшого розуміння і кращого запам’ятовування мовного матеріалу.
Майндмепінг: інструменти для розвитку креативності
Keywords: visualization; information; mind mapping; education; technology; language competence; intelligence maps; візуалізація; інформація; майндмеппінг; освіта; технологія; мовна компетенція; інтелект-карти